Understanding Six-Membered NHC-Copper(I) Allylic Borylation Selectivity by Comparison with other Catalysts and Different Substrates - Jo, Minyoung; Rivalti, Daniel; Ehle, Andrew R.; Dragulescu-Andrasi, Alina; Hartweg, Manuel; Shatruk, Michael; McQuade, D. Tyler (Synlett, 2018)
We recently introduced a family of 6-NHC-Cu(I) catalysts that exhibit highest selectivities (regio- and enantio-) exclusively when aryl ethers are used as the leaving group. Understanding the match between a catalyst and leaving group remains elusive. We sought to increase our understanding of this system by comparing our catalyst’s activity with other catalysts using substrates that contain different leaving groups. Our objective is to better understand the regioselectivity–leaving group combinations. We also observed that our catalyst functioned best when methanol was used as an additive. We examined the selectivities as a function of other protic additives. Finally, we wanted to understand the regioselectivity–enantioselectivity relationship with regards to internal versus terminal leaving groups. Overall, we demonstrate that matching leaving group and catalyst is important and that for our extended aromatic ligand the use of aromatic leaving groups is a unique pairing. We also demonstrate that the leaving group is also critical for controlling both types of selectivity.
Keywords: N-heterocyclic carbenes; copper catalyst; regioselectivities; enantioselectivities; allylic borylation